Pelatihan Media Literasi Digital Bagi Pengelola “Buruan Sae” Di Kelurahan Palasari Bandung - Zubair, Feliza (Jurnal Kajian Budaya dan Humaniora, 2023)
Buruan SAE (Healthy, Natural, Economical) is an integrated urban farming program initiated by the food and agriculture office (DISPANGTAN) of Bandung City. The SAE Hunt Program itself aims to overcome and improve food problems in the city of Bandung, by utilizing existing yards or yards by gardening to meet their respective food needs. Palasari Village, Cibiru District, Bandung City is one of the villages that has succeeded in developing the Buruan Sae program, but in its implementation, the managers feel that there is still a lack of accurate information they have obtained regarding the management of Buruan Sae, especially from social media. Seeing this reality, the PPM KKNM Unpad 2023 team held a seminar on "Digital Literacy Media Training / Information Literacy for the "Buruan Sae" Management Community in Improving Food Security in Palasari Village, Cibiru District, Bandung City". The methods used are lectures, discussions. This training aims to improve the understanding of Buruan Sae managers about media literacy so that they can identify, access, evaluate information and use it effectively in the development of Buruan Sae. The result achieved was an increase in participants' knowledge of digital media literacy. It is shown by comparing the participants' pre-test and post-test results during the training.